Staff Guidance Note on the Implementation of Public Debt Limits in Fund-Supported Programs. (Policy Papers; Policy Paper, 2015)
In December 2014, the Executive Board approved new guidelines on the use of public debt limits in Fund-supported programs. The new guidelines enter into effect on June 30, 2015. The key changes with respect to the existing debt limits policy include, inter alia, the broadening of the policy to encompass all public debt rather than only external public debt; an integrated treatment of external public debt, covering both concessional and non-concessional debt; and closer links between public debt vulnerabilities and the use and specification of public debt conditionality. This note provides operational and technical guidance related to the implementation of the debt limits policy. In particular, it sets out how the policy should be implemented in country-specific circumstances. Full text also available in French.